In-store arousal and consumers' inferences of manipulative intent in the store environment. Issue 5 (11th May 2015) - Lunardo, Renaud; Roux, Dominique
Abstract : Purpose: – The purpose of this article is to show how consumers' inferences of manipulative intent mediate the effects of in-store arousal on pleasure and approach behavior. Design/methodology/approach: – A qualitative study identifies arousal as a dimension of the store environment that may lead to inferences of manipulative intent. An experiment manipulating arousal tests the mediating effect of inferences of manipulative intent on the relationship of arousal with pleasure and approach behavior. Findings: – A qualitative study and the results of an experiment suggest that arousing store environments lead to negative outcomes when consumers infer that such environments are manipulative. The experimental study results show that high in-store arousal increases inferences of manipulative intent, which in turn negatively affect pleasure and approach behaviors. The results also indicate that the effects of in-store arousal on inferences of manipulative intent vary with age. Practical implications: – The study results recommend that practitioners carefully design their store environments, such that arousal they create does not lead consumers to believe that the environment is manipulative. Originality/value: – This article contributes to extant literature by emphasizing the crucial role of inferences of manipulative intent in the effects of in-store arousal.